O-12 Collaborating on an end of life champion model – Marie Curie and hallmark care homes. (19th November 2022) - Nugent, Melanie; Rayner, Julie; Collen, Claire; Inglis, Louise; Howard, Anne; Sinfield, Maria
Abstract : Background: On average over 50% of care home residents die within two years of admission. It is estimated that by 2035 those aged 65 years and over will account for 23% of the total population and by 2040 the most common place of death will be a care home. Against the backdrop of COVID-19 Marie Curie and Hallmark collaborated to pilot a model for increasing end of life care knowledge and skills within care home context. End of Life Champion model was developed to enhance palliative and end of life care experience within the homes alongside confidence of the end of life champions. Aims: Enhance palliative and end of life care knowledge, skills and confidence across the pilot sites with the champion model. Support end of life champions through action learning sets and mentorship. Explore different ways of working to share expertise and insight. Methods: End of Life champion model was piloted across 6 identified Hallmark Care Homes. A curriculum of learning, action learning sets, and mentorship were facilitated virtually by Marie Curie. Marie Curie and Hallmark co-designed the mentorship and action learning sets. Embedding continuous evaluation enabled reflexivity, and collaboration focusing on shared learning experience. Results: End of Life champions had high levels of engagement, action learning sets were viewed positively, further support to deliver training sessions and more time to deliver some sessions (pain management, clinical emergencies) were identified. Despite supernumerary time, team and time pressures impacted on delivery of the role. End of life champions felt that the pilot increased knowledge and skills, person-centred care, quality of conversations with families and professionals, confidence of families in the teams' abilities to provide high quality end of life care and greater oversight and quality assurance processes. Conclusion: Collaborative partnering has enabled both organisations to enhance their knowledge, skills and expertise. Enhancing the dying experience in care home settings is imperative to delivering and evidencing high quality end of life care in a culture of compassion.